Population Structure of the South West Indian Ocean Islands: Implications for Precision Medicine - Ghoorah, Anisah W.; Chaplain, Toto; Rindra, Rakotoarivony; Goorah, Smita; Chinien, Ganessen; Jaufeerally-Fakim, Yasmina (Frontiers in Genetics, 2021)
Precision medicine has brought new hopes for patients around the world with the applications of novel technologies for understanding genetics of complex diseases and their translation into clinical services. Such applications however require a foundation of skills, knowledge and infrastructure to translate genetics for health care. We discuss here why it is vital to prioritize genomics data for the South West Indian Ocean region where a mosaic of ethnicities co-exist. The islands of the SWIO, which comprise Madagascar, La Reunion, Mauritius, Seychelles and Comoros, have been the scene for major explorations and trade since the 17th century being on the route to Asia. Today’s demography of the islands is a diverse mix of ancestries including European, African and Asian. Isolation and small population sizes have likely resulted in reduced genetic variation and possible founder effects. There is a significant prevalence of diabetes, particularly in individuals of Indian descent, while breast and prostate cancers are on the rise. The island of La Reunion has a demography comparable to that of Mauritius but with a predominantly mixed population and a smaller proportion of people of Indian descent. People of Madagascar are of mixed African-Indonesian ancestries. With the rapid progress in genomic medicine, there is a growing demand for sequencing services in the clinical settings. It is a priority to generate genome sequence data to understand the population sub-structures and identify specific pathogenic variants among the different groups of inhabitants on the islands to advise families at risk and propose diagnostic screening measures.